2009
DOI: 10.1016/j.hrtlng.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an early recovery telehealth intervention on physical activity and functioning after coronary artery bypass surgery among older adults with high disease burden

Abstract: Background Older adults with poor functioning preoperatively are at risk for delayed recovery and more impaired outcomes following CABS. Purpose To determine if a 6-week early recovery telehealth intervention, designed to improve self-efficacy and management related to symptoms following CABS, was effective in improving outcomes (physical activity, physiological and psychological functioning) for older adults (> 65 years old) with higher disease burden. Design A descriptive, repeated measures experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 69 publications
1
47
0
Order By: Relevance
“…Objective measures were used in 12 of the studies reviewed while self-report were used in 32 studies 28 31 32 34–38 40–48 50 51 53–55 57–61 63 64 66 69 70. Six studies used multiple measures29 33 39 47 52 62 and three studies used a combination of objective measures and self-report 29 33 39…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Objective measures were used in 12 of the studies reviewed while self-report were used in 32 studies 28 31 32 34–38 40–48 50 51 53–55 57–61 63 64 66 69 70. Six studies used multiple measures29 33 39 47 52 62 and three studies used a combination of objective measures and self-report 29 33 39…”
Section: Resultsmentioning
confidence: 99%
“…There were 32 studies that measured PA via self-report 28 29 31–48 50 51 53–55 57–61 63 64 66 69 70. Among those using self-report, four studies used multiple measures,29 33 39 47 with three of them also using objective measures,29 33 39 and the remaining study utilising two different self-reports 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Center for Connected Health has indicated that the use of telehealth, remote patient monitoring, and disease management approaches can promote patient adherence, engagement, and improved clinical outcomes (Monegain 2009). Another study found that a telehealth intervention was able to increase older adults' physical functioning following coronary artery bypass surgery, an important aspect of preventing further mortality and morbidity (Barnason et al 2009). Researchers have also found success using online programs for older adults, such as a six-month Internet-based program for diabetic adults ages 60 and older that resulted in significant reductions in HbA1c, weight, and cholesterol levels and HDL improvement compared to a control group (Bond et al 2007).…”
Section: Section III Improved Health Outcomes: Results Of Successfulmentioning
confidence: 99%
“…Among these 64 papers were excluded for the following reasons: 35 because the ICTs used were not aimed to rehabilitation purposes ; eight papers were protocols of ongoing studies and results were not available [52][53][54][55][56][57][58][59] ; seven studies did not have a control group [60][61][62][63][64][65][66] ; five because the intervention setting was the same in the two groups 8,[67][68][69][70] ; five were pilot studies [71][72][73][74][75] ; two were secondary analysis of RCTs already included 76,77 ; two studies were excluded because the poor reporting precluded any possible assessment of its eligibility 78,79 . Finally, 12 RCTs for a total of 1047 participants were included in the review ( Figure 1).…”
Section: Studies Selectionmentioning
confidence: 99%